2018
DOI: 10.1016/j.jesp.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Bridging racial divides: Social constructionist (vs. essentialist) beliefs facilitate trust in intergroup contexts

Abstract: Trust serves as the foundation for social harmony and prosperity, but it is not always easy to build. When people see other groups as different, e.g., members of a different race or ethnicity, the perceived boundary often obstructs people from extending trust. This may result in interracial conflicts. The current research argues that individual differences in the lay theory of race can systematically influence the degree to which people extend trust to a racial outgroup in conflict situations. The lay theory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 108 publications
(146 reference statements)
5
25
0
Order By: Relevance
“…On the other hand, racial nominalism is the notion that races were created and are maintained through social, historical, and political circumstance; for example, the idea that race was developed as a way to rationalize slavery (Kvaale & Haslam, 2015; Sundstrom, 2002; Tawa, 2018). The impact of racial nominalism on intergroup outcomes has been scantly observed; moreover, the research that has been conducted on racial nominalism has tended to assess the extent to which racial essentialism is not endorsed (Kung et al, 2018; No et al, 2008; Shih, Bonam, Sanchez, & Peck, 2007), rather than directly measure racial nominalism. We argue here that racial nominalism is an active belief in its own right, not merely the absence or rejection of essentialism; in fact, there may be more than one type of racial nominalism.…”
Section: Belief In Racial Nominalismmentioning
confidence: 99%
“…On the other hand, racial nominalism is the notion that races were created and are maintained through social, historical, and political circumstance; for example, the idea that race was developed as a way to rationalize slavery (Kvaale & Haslam, 2015; Sundstrom, 2002; Tawa, 2018). The impact of racial nominalism on intergroup outcomes has been scantly observed; moreover, the research that has been conducted on racial nominalism has tended to assess the extent to which racial essentialism is not endorsed (Kung et al, 2018; No et al, 2008; Shih, Bonam, Sanchez, & Peck, 2007), rather than directly measure racial nominalism. We argue here that racial nominalism is an active belief in its own right, not merely the absence or rejection of essentialism; in fact, there may be more than one type of racial nominalism.…”
Section: Belief In Racial Nominalismmentioning
confidence: 99%
“…Nonetheless, it is possible that in other contexts, such as a more competitive distributive negotiation, displays of happiness may be useful in inducing more cooperative exchanges and rapport with the partner (Kopelman et al, 2006). These are exciting nuances that future research will benefit from manipulating the negotiation contexts and measuring subjective outcomes (e.g., trust, relationship satisfaction; Kung et al, 2018) to more fully understand the moderating role of contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Across a wide range of studies, social psychologists have sought to document the pernicious consequences of using an essentialist theory to understand social-group differences. Specifically, they have shown that an essentialist compared with a contextual theory leads to increased stereotyping and race-based categorization (Bastian & Haslam, 2006; Chao, Hong, & Chiu, 2013; Keller, 2005), less identification and perceived similarity across different groups (No et al, 2008), and lower levels of intergroup trust and desire for intergroup contact (Kung et al, 2018; Lee, Wilton, & Kwan, 2014; M. J. Williams & Eberhardt, 2008).…”
Section: Constructing the Meaning Of Difference As Essential Or Contementioning
confidence: 99%